2019
DOI: 10.2807/1560-7917.es.2019.24.36.1900013
|View full text |Cite
|
Sign up to set email alerts
|

The United Kingdom Field Epidemiology Training Programme: meeting programme objectives

Abstract: IntroductionMost evaluations of field epidemiology training programmes (FETP) are limited to process measures, but stakeholders may need evidence of impact.ObjectiveTo ascertain if the United Kingdom (UK) FETP met its objectives to: (i) strengthen capacity and provision of national epidemiology services, (ii) develop a network of highly skilled field epidemiologists with a shared sense of purpose working to common standards and (iii) raise the profile of field epidemiology through embedding it into everyday he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…Their impact can be most apparent in situations of conflicts and crises that disrupt public health systems and especially within the current shortage of resources. Several examples have clearly shown the success of FETP in responding to emergencies and disasters (9)(10)(11)(13)(14)(15)(16)(17)(18)(19)(20). During the outbreak of the Middle East respiratory syndrome (MERS) in 2014 in Saudi Arabia, FETP graduates tackled numerous issues, including but not limited to, related to redesigning the system to enable simultaneous real-time electronic reporting of suspected and confirmed cases to public health professionals who needed to take essential control and preventive actions on new cases (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their impact can be most apparent in situations of conflicts and crises that disrupt public health systems and especially within the current shortage of resources. Several examples have clearly shown the success of FETP in responding to emergencies and disasters (9)(10)(11)(13)(14)(15)(16)(17)(18)(19)(20). During the outbreak of the Middle East respiratory syndrome (MERS) in 2014 in Saudi Arabia, FETP graduates tackled numerous issues, including but not limited to, related to redesigning the system to enable simultaneous real-time electronic reporting of suspected and confirmed cases to public health professionals who needed to take essential control and preventive actions on new cases (16).…”
Section: Discussionmentioning
confidence: 99%
“…There are some studies that evaluated the FETPs and reported the experiences and the lessons learned. These studies showed that the training programs have contributed to the development of a skilled workforce in field epidemiology (9)(10)(11). However, they indicated that further efforts are required to scale up the program.…”
mentioning
confidence: 99%
“…Their impact can be most apparent in situations of con ict and crises that disrupt public health systems and especially within the current shortage of resources. Several examples have clearly showed the success of FETP in responding to emergencies and disasters (8)(9)(10)(12)(13)(14)(15)(16)(17)(18)(19). During the Middle East Respiratory Syndrome (MERS) outbreak in 2014 in Saudi Arabia, FETP graduates tackled numerous issues, including but not limited to, to redesigning the system to enable simultaneous real-time electronic reporting of suspected and con rmed cases to public health professionals who needed to take essential control and preventive actions on new cases (14).…”
Section: Discussionmentioning
confidence: 99%
“…There are some studies that evaluated FETPs and reported the experiences and lessons learnt. These studies showed that the training programs have contributed to the development of a skilled workforce in eld epidemiology [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Symptomatology includes nausea, vomiting, diarrhoea and abdominal pain, achieving full recovery after 3 days (Yasumoto et al 1978 ; EFSA 2008 ). Exposure to DSP has been frequently reported in various countries (Young et al 2019 ; Vale 2020 ), representing the primary cause of bans on the harvesting of aquaculture in Japan and Europe (Reguera et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%